To solve the inequality \( 2x - 6 \leq 7 \), follow these steps:
-
Add 6 to both sides to isolate the term with \( x \): \[ 2x - 6 + 6 \leq 7 + 6 \] This simplifies to: \[ 2x \leq 13 \]
-
Divide both sides by 2 to solve for \( x \): \[ \frac{2x}{2} \leq \frac{13}{2} \] This gives: \[ x \leq \frac{13}{2} \]
-
Convert \(\frac{13}{2}\) to a decimal or mixed number if needed: \[ \frac{13}{2} = 6.5 \]
So, the solution to the inequality \( 2x - 6 \leq 7 \) is: \[ x \leq 6.5 \]
This means that \( x \) can be any number less than or equal to 6.5.